UHPLC-Q-Orbitrap HRMS-based Untargeted Metabolomics of Sida rhombifolia Leaves and Stem Extracts - Alfi Hudatul Karomah; Mohamad Rafi; Dewi Anggraini Septaningsih; Auliya Ilmiawati; Utami Dyah Syafitri; Nanik Siti Aminah; Muhamad Insanu; Abdul Rohman (HAYATI Journal of Biosciences, 2023)
Sida rhombifolia, also known as sidaguri in Indonesia, is a medicinal plant commonly used as a herbal medicine because of its metabolite and biological activities. One of the several factors that affect plant metabolite composition and concentration is the use of plant parts. In this study, the experiment aimed to identify the metabolite profile in the leaves and stem extracts of S. rhombifolia using UHPLC-Q-Orbitrap HRMS-based untargeted metabolomics. The samples were distinguished by principal component analysis (PCA). Extraction of metabolites was conducted by sonication for approximately 30 min with 70% ethanol as the extraction solvent; 28 metabolites were identified. Seven metabolites were identified only in the leaves, three were identified only in the stems, and 18 other metabolites were identified in both the leaves and stems. These metabolites were categorized as flavonoids, triterpenoids, alkaloids, coumarins, phenolic aldehydes, phenolic acids, ecdysteroids, fatty acids, and monoterpene lactones. Based on the classification results, PCA grouped the leaves and stem extracts of S. rhombifolia using the peak area variables of the identified metabolites.